IMPLEMENTATION OF AMANAH AND ADAMUL GHARAR PRINCIPLES IN ONLINE TRADING PRACTICES AMONG SMALL AND MEDIUM ENTERPRISES IN RANAI CITY - Tomy Alpiansyah; Januariusdi; Nikmatul Rahmah Isnaniah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine the implementation of the principles of amanah (trustworthiness) and adamul gharar (absence of uncertainty) in online trading practices among small and medium enterprises (SMEs) in Ranai City, as well as to identify the underlying factors that shape such practices amid the limited theoretical understanding of Islamic economics among the business actors. This study employs a qualitative approach with a case study design, utilizing in-depth interviews, observation, and documentation as data collection techniques. Data analysis was conducted using the interactive model proposed by Miles, Huberman, and Saldaña, while data validity was assessed through the criteria established by Lincoln and Guba. The findings reveal that the principles of amanah and adamul gharar have been factually manifested through honest product presentation, transparent transactional communication, and consistency between digital information and the actual condition of goods. These practices are not grounded in formal muamalah literacy, but rather emerge organically from strong local community social bonds, cultural internalization of religious values, digital market reputation pressure, and the normative influence of informal trader networks. These findings contribute to contemporary Islamic economic discourse by demonstrating that muamalah values can be realized through cultural pathways without requiring formal theoretical prerequisites, while simultaneously supporting the achievement of SDG 8 and SDG 10 through a fair and sustainable digital trading ecosystem.